Beyond negritude : essays from Woman in the city - Nardal, Paulette, 1896-1985 (SUNY series, philosophy and race., 2009)
"In the aftermath of World War II, Paulette Nardal, the Martinican woman most famously associated with the Negritude movement and its founders Aimé Césaire, Léopold Senghor, and Léon Damas during Paris's interwar years, founded the journal Woman in the City. This annotated translation, with an introduction and essay summaries by T. Denean Sharpley-Whiting, collects work from that journal, and presents it in both the original French and in English. Never before translated, these essays represent a lens through which to view the evolution of Nardal's intellectual thought on race, gender, politics, globalization, war, religion, and philosophy. The journal's arrival announced Martinican women entering the public sphere--the city--and from its internationalist perspectives, the world stage where they would take up their responsibilities as citizens of their little island and the greater French Republic. Published from 1945 to 1951, it was, with its Christian humanist undertones and feminist inclinations, the first theologically and philosophically woman-centered liberationist journal in print"--Publisher description.